РОЗВИТОК КРЕАТИВНОСТІ МАЙБУТНЬОГО ФАХІВЦЯ ЗА ДОПОМОГОЮ ПЕРЕТВОРЕННЯ НАВЧАЛЬНОГО МАТЕРІАЛУ (Педагогіка вищої та середньої школи, 2008)
At this article is considered mechanisms of self-development creativity of future specialists as natural basic of their creative using of the professional functions in own activity with the help of changing educational information in educational process.